SIKAP DAN KEPUASAN KONSUMEN TERHADAP PRODUK OTAK-OTAK IKAN TENGGIRI DI KECAMATAN KOTAAGUNG KABUPATENTANGGAMUS (Kasus pada Otak-otak ikan tenggiri Ci Awa) - Hikmah Awaliyah; Wuryaningsih Dwi Sayekti; Teguh Endaryanto (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
The research aims to analyze the characteristics, attitudes and satisfaction of customers on mackerel fish“otak-otak”, as well as the relationship between consumer attitudes and consumercharacteristics. This study uses a survey method. The research location was home industry Ci Awa Kotaagung District of Tanggamus Regency. The determination of the location is done deliberately with the consideration that Kotaagung District is the largest fish-producing center and there are many fish-based home industries.  Respondents were 54 customers. The results of thestudy showed that consumers of Ci Awa are mostly female, age group of 17-35,high school graduates, self-employed workers, and the amount of income per month belongs to the moderate income group. Consumer attitudes towards Ci Awa's were positive. The levelof satisfaction of  customers of Ci Awa was in the satisfied category. Consumer characteristics (age,income, and education) have a relationship with the attitude of consumers of Ci Awa.Key words: attitudes, consumer, home industry.